Objetos de ciências e tecnologia (C&T) do centro de memória da ciências e da tecnologia de Sergipe: interface para o ensino de ciências por meio de uma abordagem histórica - Santana, Jamile dos Santos (2022)
The debate about the limitations of a so-called “traditional” scientific education model to work in an information and knowledge society has been triggering discussions about the needs of innovation and curriculum production with new ways of teaching science. In the midst of this context of curricular reforms, the History of Science, through a contextualized approach within a perspective of science presents itself as a possibility to promote a teaching capable of relate significantly discussions to and about science. In this context, this research presents the interfaces of the History of Science as an alternative for the promotion of scientific literacy. We present the assumption that the history “behind” science and technology (S&T) objects can contribute to the teaching and learning process of scientific content related to them. As a case study, we consider the objects present in the museum of Instituto Tecnológico e de Pesquisa do Estado de Sergipe (ITPS) through a pedagogical perspective that seeks to answer, based on the results found in the literature, how the S&T objects found can contribute for the teaching process. The present work is characterized as bibliographic and structured according to the ideas of research in development, or Design Research.